BULLYING DAN KESEHATAN MENTAL PADA REMAJA SEKOLAH MENENGAH ATAS DI BANDA ACEH - Faizah, Firsta; Amna, Zaujatul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2017)
Bullying is a form of adolescent’s negative behavior that continues to increase in school. The involvement of adolescents as the bullies are related to the mental health condition. This study aimed to find the correlation between bullying and mental health on student high school in Banda Aceh. 400 adolescents in Banda Aceh (265 females and 135 males) were invited to participated in the study were using Multi-stage Cluster and Disproportionate Stratified Random Sampling. The data was collected using The Revised Olweus Bully/Victim Questionnaire (OBVQ) and Mental Health Inventory-38 (MHI-38). The data was analyzed using nonparametric statistic with Spearman’s Rho correlation technique. The result showed that the value of correlation coefficient (r) = -0,157 with significant value (p) = 0,002 (p